Laparoscopic management of ureter stones, comparison of two techniques - Aydin, Cemil; Akkoc, Ali (Annals of Medical Research, 2021)
Aim: With the improvement of minimally invasive urology procedures, open surgical interventions are less common to treat ureteral calculus. Laparoscopic ureterolithotomy (LU) indications are large multiple and/or impacted ureteral calculus that may not be treated with shock-wave lithotripsy or ureterorenoscopy approaches. In this study, we aimed to compare laparoscopic retroperitoneal and transperitoneal ureterolithotomy techniques in terms of perioperative-postoperative results. Materials and Methods: We reviewed 45 patients with large and impacted upper ureter calculus who underwent transperitoneal or retroperitoneal LU between January 2012 and December 2017. The transperitoneal and retroperitoneal routes were grouped as group 1 and 2, respectively. Groups were crosschecked according to preoperative, intraoperative, and postoperative clinical datum. Results: We did not find statistically meaningful disparity between groups with regards to age, gender, stone size, blood loss and body mass index. The stone free accomplishment ratio was 100% in group 1 and 2. Visual analogue scale scores were higher and statistically meaningful in group 1 (p<0.05). The mean operative time was statistically shorter in group 2 (p:0.022). No double J stent inserted routinely intraoperatively. Conclusion: Compared to those obtained with the transperitoneal technique, the retroperitoneal technique has a significantly shorter operating time and less postoperative pain for large and impacted proximal ureteral calculus. More randomized, controlled and prospective studies on large samples are needed.